DEGRADATION OF POLYCYCLIC AROMATIC HYDROCARBONS (PAHS) IN PRODUCED WATER BY ELECTROCHEMICAL OXIDATION - YAQUB, ASIM (2015)
Produced water is a wastewater stream associated with oil and gas exploration and production. lt contains significant amount of polycyclic aromatic hydrocarbons (PAHs), which are not treatable by conventional methods. Electrochemical oxidation is an advanced oxidation process that has shown potential to be an effective treatment alternative for wastewater containing toxic substances. However, high cost electrodes boron doped diamond (BDD), platinum, tantalum etc. hinders the large scale application of electrochemical process. The present study focused on the development of effective anode material and experimentally determines the optimal conditions for the application of electrochemical oxidation for degradation of P AHs in produced water.